Bioactive glycoalkaloides isolated from Solanum melongena fruit peels with potential anticancer properties against hepatocellular carcinoma cells - Fekry, Mostafa I. (Sci Rep, 2019)
Hepatocellular carcinoma (HCC) is progressively increasing tumor with lack of accurate prognosis and inadequate systemic treatment approaches. Solanum sp. (such as Solanum melongena) is a folk herb which is reported to possess anticancer properties. In a continuity for our interest in pursuing the anticancer activity of compounds isolated from the fruit peels of Solanum melongena, the HPLC profiling and ESI-MS assessment for the methanolic extract evidenced the presence of bioactive glycoalkaloids (solasonine, solasodine and solamargine). These glycoalkaloids were isolated, purified and proved to possess in vitro cytotoxicity against human liver cancer cell lines (Huh7 and HepG2). Herein, we investigated the potential mechanism of action of these compounds using DNA content flow-cytometry and apoptosis/necrosis differential anaylsis using annexin-V/FITC staining. Solasonine, solasodine and solamargine inducd significant antiproliferative effect against liver cancer cells (Huh7 and HepG2) which was attributed to cell cycle arrest at S-phase. Solamargine, solasodine and solasonine induced significant apoptosis in Huh7 cells. Only solamargine-induced cell cycle arrest, was reflected as apoptotic cell killing effect against HepG2 cells. In conclusion, glycoalkaloids derived from Solanum melongena and particularly, solamargine are promising antiproliferative agents with potential anticancer effects.